Elaboración de un manual de calidad para reducir el porcentaje de productos defectuosos en los procesos de producción de la cooperativa cafetalera los ángeles - Cedeño Vera, Ruth Noemi (2023)
This research was conducted at the Los Angeles Coffee Cooperative in order to develop a quality manual to reduce the percentage of defective products resulting from production processes. Initially, a detailed analysis of current practices was carried out through interviews, flowcharts and cooperative mapping practices. This highlighted flaws in the critical drying stage, where the use of traditional methods exposed to climate variability affects final grain quality. Subsequently, the level of compliance with the requirements of the ISO 9001:2015 standard was evaluated through a comprehensive checklist, determining that implementation was almost null, at just 16.82%. This very wide gap demonstrates the absence of a formal quality management system and standardized practices. A quality manual, a procedures manual and an instruction manual were developed. The first establishes the general policies and guidelines; the second standardizes critical processes such as drying and hulling; and the third standardizes equipment use. Its consistent implementation, together with continuous training and sustained managerial commitment, can lay a solid foundation for advancing towards a quality culture, reducing defective products, and improving customer satisfaction.